Peningkatan Pemahaman Siswa Tentang Integrasi Nasional Melalui Sosialisasi Pencegahan Aksi Tawuran di Sekolah Menengah Pertama Negeri 30 Kota Padang - Engrina Fauzi; Elwidarifa Marweny; Irsyad Firmansyah; Muhammad Farel Adha; Zacky Lisandro; Putri Maharani; Joy Simamora; Zahwatul Husna; Renata Sari (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
The Law Study Program, Faculty of Law, Social Sciences and Humanities, Dharma Andalas University carried out a socialization activity at State Junior High School 30 Padang City with the theme of National Integration and Its Relation to Brawl Actions. This activity aims to provide students with an understanding of the importance of national integration as an effort to strengthen national unity and integrity while preventing destructive actions, such as brawls. The approaches used include interactive lectures, quizzes, and games. And this socialization aims to build collective awareness among students regarding the negative impacts of brawls and the importance of living in harmony in diversity. This program is expected to be the first step in creating a conducive, harmonious, and violent school environment. As an effort to overcome brawls between students, it can be done in Penol and non-Penol ways. Among others, eradication, prevention, and action.